Effects of COVID-19-targeted nonpharmaceutical interventions on children's respiratory admissions in China: a national multicenter time series study. (November 2022) - Wang, Xinyu; Xu, Hui; Chu, Ping; Zeng, Yueping; Tian, Jian; Song, Fei; Guo, Yongli; Xu, Xin; Ni, Xin; Feng, Guoshuang
Highlights: Our results suggest that nonpharmaceutical interventions (NPIs) reduce children's respiratory admissions significantly. The effect of NPIs is most drastic for pneumonia among children of all ages. The effect is most drastic for children aged 4-6 and 7-12 years. NPIs may be used to further prevent admissions for children's respiratory infections. Abstract: Objectives: To estimate the impact of nonpharmaceutical interventions (NPIs) targeted at the COVID-19 pandemic on the admission number of respiratory diseases, including pneumonia, acute bronchitis & bronchiolitis, and acute upper respiratory infections (AURIs) for children in China. Methods: Continuous hospitalization records aged 0-18 years from January 1, 2016, to December 31, 2020, were collected from 26 tertiary children's hospitals. Interrupted time series analysis with a quasi-Poisson model was conducted with the start time of the COVID-19 pandemic as the interrupted timepoint and the weekly admission numbers of all-cause respiratory disease, pneumonia, acute bronchitis & bronchiolitis, and AURI as the outcome measures. Hospitalizations of childhood neoplasms were analyzed as the reference group. Results: The reduction in admission numbers following NPIs was -55.0% (-57.9 to -51.9%) for all-cause respiratory diseases, -62.7% (-65.7 to -59.5%) for pneumonia, -48.1% (-53.3 to -42.3%) for bronchitis & bronchiolitis, and -24.3% (-28.6 to -19.8%) for AURI. The effect estimates of NPIs on childhood neoplasms was -29.1% (-33.6 to -24.4%). Stratification analysis showed the reduction was most drastic for children at 4-6 and 7-12 years. Conclusion: The admission number for respiratory diseases among children in China decreased drastically after the implementation of NPIs. NPIs with low socio-economic burdens should be suggested even outside the COVID-19 pandemic.